2010
DOI: 10.1093/pasj/62.2.347
|View full text |Cite
|
Sign up to set email alerts
|

Subaru Near-Infrared Imaging of Herbig Ae Stars*

Abstract: We report results of $H$-band ($\lambda =$ 1.65$ \mu$m) imaging observations of young intermediate-mass stars using the Subaru 8.2-m Telescope with the adaptive optics AO36 and the infrared coronagraph CIAO. The targets consist of 16 Herbig Ae/Be stars (15 Herbig Ae stars and one Herbig Be star) and four additional main-sequence stars with infrared excesses. Five protoplanetary disks have been spatially resolved around the Herbig Ae stars with ages of 2–8 Myr. The resolved disks have outer radii of several 100… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
45
3

Year Published

2013
2013
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(57 citation statements)
references
References 127 publications
9
45
3
Order By: Relevance
“…Also no clear indication of SiO gas can be found in the residuals of the IRS spectra. Further, such collisions are less likely in the gas disks found in our sample Fukagawa et al 2010;Brown et al 2012;Andrews et al 2009, and references therein) than in a gas-poor debris disk like HD 172555 since the interaction between disk and planetesimals will dramatically reduce the eccentricity of orbits (Bitsch & Kley 2010).…”
Section: Formation History Of the Forsterite Grainsmentioning
confidence: 82%
See 1 more Smart Citation
“…Also no clear indication of SiO gas can be found in the residuals of the IRS spectra. Further, such collisions are less likely in the gas disks found in our sample Fukagawa et al 2010;Brown et al 2012;Andrews et al 2009, and references therein) than in a gas-poor debris disk like HD 172555 since the interaction between disk and planetesimals will dramatically reduce the eccentricity of orbits (Bitsch & Kley 2010).…”
Section: Formation History Of the Forsterite Grainsmentioning
confidence: 82%
“…Harker & Desch 2002). Given that all of our targets are still gas-rich Fukagawa et al 2010;Brown et al 2012;Andrews et al 2009, and references therein), small dust grains should be efficiently heated to high temperatures at disk radii of up to at least ∼10 AU.…”
Section: Formation History Of the Forsterite Grainsmentioning
confidence: 99%
“…Guimarães et al (2006) Juhász et al 2010). The disk around HD 163296 has been spatially resolved (e.g., Grady et al 2000;Fukagawa et al 2010;Sandell et al 2011;Garufi et al 2014), which is extended to ∼ 440 AU and shows a broken ring structure. Asymmetric supersonic jets associated with HD 163296 are found, which are roughly perpendicular to the disk plane (e.g., Devine et al 2000;Wassell et al 2006).…”
Section: A32 Hd 144432mentioning
confidence: 99%
“…-(1) Alecian et al (2013), (2) Rigliaco et al (2015), (9) Sturm et al (2013), (10) Seok & Li (2015), (11) Maaskant et al (2014), (12) Juhász et al (2010), (13) Fairlamb et al (2015), (14) Mariñas et al (2011), (15) Verhoeff et al (2012), (16) van Boekel et al (2005), (17) Siebenmorgen et al (2000), (18) Hubrig et al (2009), (19) Folsom et al (2012, (20) Fukagawa et al (2010), (21) Seok & Li (2016), (22) Keller et al (2008), (23) Merín et al (2010), (24) Harvey et al (1984), (25) Kóspál et al(2012), (26) Boersma et al (2009), (27) Brown et al (2008), (28) Borges Fernandes et al (2007, (29) Schütz et al (2009), (30) Prato et al (2003), (31) Jeffers et al (2013), (32) Huélamo et al (2011), (33) Casey et al (1998), (34) Pinilla et al (2014), (35) Magazzu et al (1991), (36) Liu et al (2011), (37) …”
mentioning
confidence: 99%
“…Considering the spectral type, the A7 III source HD 142666 is a Herbig Ae/Be object while the other two sources are T Tauri objects. HD 142666 is assumed not to have any stellar companion (e.g., Fukagawa et al 2010). Considering our interferometric measurements, a sinusoidal visibility spectrum could not be found that would be characteristic of a close (stellar) companion in both systems.…”
Section: Object Samplementioning
confidence: 99%